2020
DOI: 10.3102/0013189x20909823
|View full text |Cite
|
Sign up to set email alerts
|

Social Studies Teacher Perceptions of News Source Credibility

Abstract: Politically tumultuous times have created a problematic space for teachers who include the news in their classrooms. Few studies have explored perceptions of news credibility among secondary social studies teachers, the educators most likely to regularly incorporate news media into their classrooms. We investigated teachers’ operational definitions of credibility and the relationships between political ideology and assessments of news source credibility. Most teachers in this study used either static or dynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 34 publications
1
19
0
2
Order By: Relevance
“…It should be kept in mind that a postgraduate programme has given an additional competence to an undergraduate degree, but it does not replace it, so that, it is not only the teacher's postgraduate degree important, his or her entire training background should determine which area of knowledge should be assigned him/her to work in. As a result, faculties will gradually generate the teaching staff, according to an appropriate academic management of the faculty, proposes [32].…”
Section: Layer 1 -Physical Record the Experiences Of Other Heismentioning
confidence: 99%
“…It should be kept in mind that a postgraduate programme has given an additional competence to an undergraduate degree, but it does not replace it, so that, it is not only the teacher's postgraduate degree important, his or her entire training background should determine which area of knowledge should be assigned him/her to work in. As a result, faculties will gradually generate the teaching staff, according to an appropriate academic management of the faculty, proposes [32].…”
Section: Layer 1 -Physical Record the Experiences Of Other Heismentioning
confidence: 99%
“…Psychological research on adults finds that individuals prefer news that agrees with their political or ideological views (Iyengar & Hahn, 2009) and that evaluations of news quality tend to depend on how favorable/unfavorable stories are to the reader's preferred group (Kelly, 2019). Previous research has found that teachers' evaluation of a news source's credibility is related to their perceived ideological similarity with the source (Clark et al, 2020). Given these results, it is likely that teachers are influenced in some way by ideology when they choose what news media they use in their classroom.…”
Section: Teacher Choices About Current Events and News Contentmentioning
confidence: 99%
“…Among the small group of teachers who reported using this website, those who identified their ideology labeled themselves "very conservative." Breitbart is an unreliable news source because it does not meet standards of journalistic ethics, but it is likely that teachers who use Breitbart in their classrooms find it acceptable because it aligns with their personal political views (Clark et al, 2020;Kelly, 2019).…”
Section: Ideology and Teaching Current Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…It seems that the majority of the students are more willing to use Internet search engines than library catalogues. Additionally, it can be difficult for student teachers to evaluate the trustworthiness of the information they find online (Clark et al, 2020;Sawyer & Myers, 2018). Student teachers, therefore, need support to develop strategies for online search and navigation (Clark et al, 2020).…”
Section: Perception Of Preparedness To Exercise Responsible Use Of Icmentioning
confidence: 99%